2018
DOI: 10.1177/0899764018819874
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Growth of the Nonprofit Sector: The Choice of Indicator Matters

Abstract: Interestingly, although many authors consent that nonprofit organizations and the nonprofit sector have grown in many countries, there is little discussion of how to best measure this growth. Looking at the broad universe of nonprofit organizations, there is no single measure that is relevant for the whole sector and captures changes adequately. This article gives an overview of commonly-used growth measures in the existing nonprofit literature and discusses the informative value of the various measures. Using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 46 publications
(55 reference statements)
0
10
0
1
Order By: Relevance
“…Worldwide, the number, size and prominence of non-profit organizations (NPOs) is growing [1,2]; this growth is caused by the increase of social problems [3] of an economic, political, and religious nature etc. [4] NPOs are aimed at accomplishing functions intended to strengthen the social and ecological dimensions of sustainable development [5].…”
Section: Introductionmentioning
confidence: 99%
“…Worldwide, the number, size and prominence of non-profit organizations (NPOs) is growing [1,2]; this growth is caused by the increase of social problems [3] of an economic, political, and religious nature etc. [4] NPOs are aimed at accomplishing functions intended to strengthen the social and ecological dimensions of sustainable development [5].…”
Section: Introductionmentioning
confidence: 99%
“…The aggregated assets, on the contrary, capture the subsector's overall size. Pennerstorfer and Rutherford (2019), for instance, showed that the correlation between the two indicators is very low even though both have been used to estimate nonprofit growth. Our results corroborate that researchers should be mindful of the indicators to estimate the growth of the nonprofit sector.…”
Section: Supplementary Analysis: the Fiscal Size Of Ecfsmentioning
confidence: 99%
“…No single indicator exists which adequately and comprehensively captures sector growth (Pennerstorfer and Rutherford 2019). Consequently, it is advisable to use alternative variables to check the robustness of the results.…”
Section: Data and Descriptive Overview Of The Austrian Nonprofit Social Services Sector 2003-2017mentioning
confidence: 99%